IMPACT OF PANDEMIC COVID-19 ON SECONDARY AND HIGHER SECONDARY LEVEL OF EDUCATION AT BALURGHAT BLOCK IN DAKSHIN DINAJPUR DISTRICT, WEST BENGAL, INDIA- A GEOGRAPHICAL APPRAISAL - Pintu Biswas (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The COVID-19 pandemic has created the largest interruption and remarkable impact on school education systems in human history. It has affected a large number of children beyond states, class, caste, gender and region. It has created many probabilities to come out of the burdensome classroom teaching model to a new era of digital model. The main purpose of the study is to investigate the impact of COVID-19 pandemic and lockdown on Secondary and Higher Secondary Level of Education at Balurghat Block. This study integrates with primary data a questionnaire-based household survey of the concerned area compelled by the author himself. Through stratified random choice 180 students have been selected (99 are male and 81 are female) among them 85 (36 from class IX and 49 from class X) pursuing secondary level and 95 (28 from class XI and 67 from class XII) pursuing higher secondary level of education in Balurghat Block. The respondents were asked to rate all the indicators on a Likert scale to resolve the degree of impact each indicator has on the respondents’ brain. In this particular study, descriptive research design was employed to gain enough insight for achievement of the desired objectives.